Intracellular silver speciation by coupling capillary electrophoresis to ICP-MS integrating a high performance spiral flow spray chamber - Men, Xue; Wu, Chengxin; Zhang, Xuan; Wei, Xing; Chen, Ming-Li; Yang, Ting; Wang, Jian-Hua (Analytica chimica acta, 2021)
The study of silver species and their distribution/transformation in cell interior is of high significance for the elucidation of toxicology of silver nanoparticles (AgNPs). The intracellular speciation of dissolved Ag(I) and AgNPs was reported. The analytical platform integrated capillary electrophoresis (CE) to inductively coupled plasma-mass spectrometry (ICP-MS) incorporating a high efficiency interface and a high performance spiral flow spray chamber (SFSC). The interface and the SFSC provide a favorable detection limit of 87 ng L−1 for the dissolved Ag(I). Total silver content was quantified by ICP-MS subject to digestion of the cell lysate, and quantification of AgNPs was carried out by subtraction. The speciation of dissolved Ag(I) and AgNPs in culture medium and HepG2 cells was performed, with RSDs of <3% for relative peak area and <2% for migration time, as well as spiking recoveries of 93.8%–94.3% in opti-MEM and 92.7%–106.6% in cell lysate. The present study indicated higher solubility of AgNPs in the cell interior with respect to that in the culture medium, due to oxidative stress or acidic microenvironment in the cancer cells. [Display omitted] •An efficient method is developed for silver speciation based on CE-ICP-MS system.•High efficiency interface and spiral flow spray chamber are designed.•Spiral flow spray chamber ensures high transport efficiency and sensitivity.•The solubility of AgNPs is higher in cell than that in culture medium.•Intracellular transformation and toxicology of AgNPs are investigated thoroughly.